Phylogenetic relationships within the Pylochelidae (Decapoda: Anomura: Paguroidea): A cladistic analysis based on morphological characters - Lemaitre, Rafael; Mclaughlin, Patsy A.; Sorhannus, Ulf (Zootaxa, 2009)
Phylogenetic relationships within the “symmetrical” hermit crab family Pylochelidae were analyzed for 41 of the 45 species and subspecies currently considered valid. In the analyses, 78 morphological characters comprised the data matrix and the outgroup consisted of Thalassina anomala, a member of the Thalassinidae, and Munida quadrispina, a member of the Galatheidae. A poorly resolved strict consensus tree was obtained from a heuristic parsimony analysis of unweighted and unordered characters, which showed the family Pylochelidae and the subfamilies Pylochelinae and Pomatochelinae to be monophyletic taxa – the latter two groups had the highest Bremer support values. Additionally, while the subgenus Pylocheles (Pylocheles) was strongly supported, the subgenera Xylocheles, and Bathycheles were not. More fully resolved trees were obtained when using implied weighting, which recognized the monotypic subfamilies Parapylochelinae, Cancellochelinae and Mixtopagurinae. The subfamily Trizochelinae was found to have four distinct clades and several ambiguously placed taxa.